A conformational epitope in placental malaria vaccine antigen VAR2CSA: What does it teach us? - Justin Y A Doritchamou; Jonathan P Renn; Lars Hviid; Patrick E Duffy (PLoS Pathogens, 2023)
VAR2CSA is the Plasmodium falciparum variant surface antigen that mediates binding of infected erythrocytes to chondroitin sulfate A (CSA) and their sequestration in intervillous spaces of the placenta, leading to placental malaria (PM). Relatively high polymorphism in VAR2CSA sequences has hindered development of a vaccine that induces broadly neutralizing immunity. Recent research has highlighted that a broadly reactive human monoclonal antibody, called PAM1.4, binds to multiple conserved residues of different subfragments of VAR2CSA, forming a conformational epitope. In this short perspective, we describe evidence that residues located in the interdomain-1 fragment of VAR2CSA within the PAM1.4 binding epitope might be critical to broad reactivity of the antibody. Future investigation into broadly reactive anti-VAR2CSA antibodies may be important for the following: (1) identification of similar conformation epitopes targeted by broadly neutralizing antibodies; and (2) understanding different immune evasion mechanisms used by placenta-binding parasites through VAR2CSA polymorphism in critical epitopes.